Identifying Involvement of H19-miR-675-3p-IGF1R and H19-miR-200a-PDCD4 in Treating Pulmonary Hypertension with Melatonin - Wang, Ran (Mol Ther Nucleic Acids, 2018)
Non-coding RNAs play an important role in the pathogenesis of pulmonary arterial hypertension (PAH). The aim of this study was to characterize the therapeutic role of melatonin as well as the underlying molecular mechanism (its effects on the expression of H19 and its downstream signaling pathways) in the treatment of PAH. Real-time PCR and western blot analysis were performed to evaluate the expression of H19, miR-200a, miR-675, insulin-like growth factor-1 receptor (IGF1R), and programmed cell death 4 (PDCD4). The value of systolic pulmonary artery pressure (SPAP) and the ratio of medial thickening in the monocrotaline (MCT) group were increased, whereas the melatonin treatment could decrease these values to some extent. The weights of RV (right ventricle), LV (left ventricle) + IVS (interventricular septal), and RV/(LV + IVS) in the MCT group were much higher than those in the MCT + melatonin and control groups. In addition, the expression of H19, miR-675, IGF1R mRNA, and IGF1R protein in the MCT group was the highest, whereas their expression in the control group was the lowest. The expression of miR-200, PDCD4 mRNA, and PDCD4 protein in the MCT group was the lowest, whereas their expression in the control group was the highest. Furthermore, H19 directly suppressed the expression of miR-200a, whereas miR-675-3p and miR-200a directly inhibited the expression of IGF1R and PDCD4, respectively. Finally, melatonin treatment inhibited cell proliferation; upregulated the expression of H19, miR-675-3p, and PDCD4; and downregulated the expression of miR-200a and IGF1R. This study demonstrated the role of H19-miR-675-3p-IGF1R- and H19-miR-200a-PDCD4-signaling pathways in the melatonin treatment of PAH.